ROBOTICS IN ISLAMIC BANKING: BIBLIOMETRIC ANALYSIS AND FUTURE RESEARCH AGENDA - Rofiul Wahyudi; Julia Noermawati Eka Satyarini; Fitria Nurma Sari (Diponegoro Journal of Islamic Economics and Business, 2026)
This study aims to map and analyze scientific developments related to robotics and artificial intelligence (AI) within the Islamic banking ecosystem using a bibliometric approach and network visualization. The analysis was conducted using Bibliometrix (RStudio) for performance analysis and VOSviewer for science mapping, encompassing networks of authors, institutions, countries, keywords (both author keywords and index keywords), and citation networks. A total of 626 Scopus-indexed articles discussing robotics and AI in the context of Islamic banking were analyzed. And the results identified three main clusters: (i) the Islamic fintech and digital transformation cluster (including fintech, blockchain, and AI), (ii) the digital/mobile banking cluster focusing on aspects of trust, cybersecurity, and customer satisfaction, and (iii) the TAM/UTAUT model-based technology adoption cluster highlighting factors such as risk perception and behavioral intention. In terms of collaboration, authors such as Rabbani and Hassan, institutions such as the Islamic Business School (UUM), and countries such as India, Malaysia, and Indonesia occupy central positions. Conceptually, connecting keywords such as fintech, mobile banking, technology adoption, artificial intelligence, and Sharia compliance form bridges between the main topics. The novelty of this research lies in the first comprehensive mapping that explicitly links robotics with the Islamic banking ecosystem, while identifying opportunities for further research in the fields of Sharia based automation, halal virtual assistants, and real time Sharia compliance monitoring.